Feasibility modeling of passive soil vapor extraction. Issue 2 (1st March 2002) - Jennings, A A; Patil, P
Abstract : Passive soil vapor extraction (PSVE) is a soil remediation process that uses ambient meteorological conditions to accomplish gas well pumping. Passive soil vapor extraction wells use simple unpowered wellheads in place of vacuum pumps or blowers. They can be used for extraction or injection pumping and can reduce the complexity and cost of either. The innate "pulse-pumping" pattern of PSVE may also help overcome mass transfer resistances within the soil. However, the meteorological conditions that drive PSVE are strongly random in magnitude and duration and produce flows that are lower than pumped soil vapor extraction (SVE). Although PSVE had been successfully field demonstrated, uncertainty about well yields and design procedures has hindered application. This manuscript presents the results of PSVE feasibility modeling. Analysis is presented to illustrate that, under appropriate conditions, PSVE can yield useful well flows. Transient gas flow analysis is required to account for meteorological boundary conditions that impact the domain on relatively fine time scales. Analysis is also presented to illustrate the impacts that non-steady flow conditions can have on contaminant mass transport. Results show that under appropriate conditions PSVE could be competitive with conventional pumped vapor extraction. Extraction rates will be lower, but may be achieved at significantly lower cost. Key words : vapor extraction, remediation, passive pumping, mass transport modeling, transient boundary conditions, feasibility analysis.